Blood gas analysis in Mangalarga Marchador horses with colic - Tiane F. Castro (Revista MVZ Córdoba, 2015)
This study aims to distinguish blood gas changes in horses with colic syndrome in which small or large intestine is affected. Materials and methods. Thirty Mangalarga Marchador horses were assessed, divided into groups according to the affected intestinal segment in episodes of colic syndrome (ECS): a group (N=10) of horses suffering from ECS with lesions only in the small intestine, a group (N=10) of horses suffering from ECS with lesions only in the large intestine and a group (N=10) of healthy horses (control). All the animals with ECS were submitted to exploratory laparotomy in order to establish the intestinal segment affected. Blood samples were collected by venipuncture, before surgical procedure to determine sodium, potassium, chloride, urea, glucose, hematocrit, hemoglobin, pH, carbon dioxide partial pressure, total carbon dioxide concentration, bicarbonate, base excess and anion gap. Results. No significant changes were found in plasma levels of Na + , K + , Cl - , pCO 2 and anion gap in any type of ECS. Horses with small intestine injuries presented higher levels of tCO 2, urea and bicarbonate compared to those with large intestine injuries and to the control group, as well as higher levels of glucose and base excess than the control group. Conclusions . Horses with colic syndrome bearing small intestine injuries show wider variations in the blood gas parameters than horses with large bowel lesions.